Integration of multi-sensors data in detecting slope movement based on threshold values - Hazwani N.K.; Rohayu C.O.; Fathoni U.; Aiman I.; Amiruddin Z.; Baharudin I.N.Z.; Rasyikin R.; Din N.M.; Hussain H.; Jamaludin M.Z.; Baharuddin Z.; Zulkarnain S.; et al. (Asian Research Publishing Network, 2023)
Malaysia has a number of power lines for electricity supply generated by Tenaga Nasional Berhad (TNB). The company has owned 95% of power lines from North to South of Peninsula Malaysia. In order to maintain the quality of power transmission for the country, it is very important for TNB to monitor the stability of their transmission towers (pylons). Unfortunately, most of these transmission towers are located at very hilly and remote areas. Conducting inspection at those areas are not efficient since the staffs are exposed to wild animals, not cost effective and always require longer inspection time due to weather condition. Therefore, a new technique which is implementing a stability threshold value by installing selected sensors at the critical slope is introduced to improve the efficiency of current slope monitoring procedure. Four (4) sensors which are piezometer, inclinometer, raingauge and soil moisture probe are installed to monitor four (4) parameters that cause landslide. Based on one-cycle (1 year) of data collection, three (3) threshold values have been identified to be as an alert value for the monitoring system. 2006-2016 Asian Research Publishing Network (ARPN).